Declaration on cervical cancer elimination: literature review and perspectives from early-career clinicians - Kacperczyk-Bartnik, Joanna; El Hajj, Houssein; Tóth, Icó; Bizzarri, Nicolò; Tóth, Richard; Razumova, Zoia; Zwimpfer, Tibor Andrea; Taumberger, Nadja; Bilir, Esra; Strojna, Aleksandra; Angeles, Martina Aida; Gasimli, Khayal; et al. (International journal of gynecological cancer, 2025)
Despite effective prevention methods, cervical cancer remains one of the most incident malignancies globally. This literature review and perspectives from early-career clinicians aim to propose actionable recommendations to reduce the global burden of cervical cancer. The authors, representing the early-career clinicians and researchers, patient representatives, epidemiologists, and gynecologic oncology experts, identified 5 key pillars for cervical cancer elimination based on literature reviews and interdisciplinary discussion: (1) raising awareness of human papillomavirus (HPV) and cervical cancer; (2) ensuring evidence-based HPV communication; (3) fostering collaboration with other specialties and organizations; (4) increasing HPV vaccination rates; and (5) improving cervical cancer screening. Achieving the World Health Organization’s cervical cancer elimination target by 2030 requires a comprehensive, multi-faceted approach. Our recommendations emphasize the need for targeted awareness campaigns, evidence-based communication, collaboration with various stakeholders, promotion of best practices, and keeping evidence of innovative interventions up-to-date, with intensified efforts in low- and middle-income countries where the burden is the greatest.
Online verfügbar: 26. April 2025, Artikelversion: 27. Mai 2025
Gesehen am 25.09.2025